Keefektifan Metode Fitoremidiasi Dengan Pemanfaatan Tanaman Kayu Apu Untuk Menurunkan Kadar Amoniak Pada Limbah Cair Rumah Sakit Umum PKU Muhammadiyah Delanggu - Saputro, Thoni; , Dwi Astuti, SKM, M.Kes; , Rezania Asyfiradayati, SKM., MPH (2016)
Liquid waste containing ammonia subtances can affect human health and the enviroment. Ammonia levels based on preliminary test result will be undertaken at the Public Hospital of PKU Muhammadiyah Delanggu of 0,483 mg/l, the result exceeded the water quality standar of waste. One of the ways that can be done to reduce levels of ammonia with fitoremidiasi method using the apu wood plant. This research study design was a true experiment with pretes and posttest with control grup. Location of researc at the Hospital of PKU Muhammadiyah Delanggu. Phytoremidiation variation uses 4 plants, 6 plants, and 8 plants apu wood done for 7 days in 15 liters of waste water. The average yield of the activity level of ammonia after the treatments is 80,565%, 85,256%, and 97,323%. The statistical test used is the One Way Anova. The result of the study obtained plants water hyacinth effectiveto reduce the ammonia on the water waste debgab doses effevtie 8 plant (p-value 0,001).